The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13061394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Stearate in the Mechanical and Physical Properties of Concrete with PCC and Fly Ash as Binders

Abstract: This work aims to study the effect of Ca(C 18 H 35 O 2 ) 2 (calcium stearate) on the properties of concrete by using Portland composite cement (PCC) and fly ash as binders. The calcium stearate content used in the concrete here consists of 0, 1, 5, and 10 kg per m 3 of concrete volume, or alternatively, 0 to 2.85% by the weight of cement. We have performed several tests for each of the contents, namely, compressive strength, water absorption, chloride ion infiltration, and accelerated corrosion tests. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…This shows that the mix proportion designed has fulfilled the 20 MPa concrete compressive strength plan. It is worth noting here that the effect of calcium stearate on compressive strength of self-compacting concrete (SCC) has been studied in [21]. The result showed that the compressive strength of SCC at grade 20 MPa decreased around 7.5% due to the addition of calcium stearate 5 kg/m 3 of concrete.…”
Section: Compressive Strengthmentioning
confidence: 96%
See 1 more Smart Citation
“…This shows that the mix proportion designed has fulfilled the 20 MPa concrete compressive strength plan. It is worth noting here that the effect of calcium stearate on compressive strength of self-compacting concrete (SCC) has been studied in [21]. The result showed that the compressive strength of SCC at grade 20 MPa decreased around 7.5% due to the addition of calcium stearate 5 kg/m 3 of concrete.…”
Section: Compressive Strengthmentioning
confidence: 96%
“…As a result, the capillaries in concrete will go down due to evaporation of free water in fresh concrete. Other comprehensive researches conducted by Maryoto et al [19][20][21] have also found that the use of calcium stearate in concrete reduces compressive strength, corrosion attacks, chloride ion infiltration, and water absorption. The reduction of corrosion attacks can also be avoided by applying an inhibitor in the reinforced concrete [22].…”
Section: Introductionmentioning
confidence: 96%
“…), acting on the reaction of oxygen on the surface of steel, or mixed inhibitors (such as materials with hydrophobic groups coupled with polar groups, organic polymers, etc. ), acting through adsorption on the steel surface and creating a protective film. ,, …”
Section: Factors Affecting the Properties Of Gpsmentioning
confidence: 99%
“…), acting through adsorption on the steel surface and creating a protective film. 79,280,281 Finally, the addition of fiber reinforcement is another viable approach to enhance the durability of cementitious systems against chemical attack, particularly after (micro)cracking, as such fibers may stitch microcracks together, minimizing the volume of continuous voids and thus leading to a reduced loss of seal integrity when cracking does occur. 33,54,56,272,276,277 In addition to their promising features as the main isolation materials, GPs have also demonstrated desirable characteristics when they are used as coating materials to protect OPC against corrosion.…”
Section: Main Mechanisms Of Corrosionmentioning
confidence: 99%
“…[20][21][22][23] However, stearic acid of high hydrophobicity and high surface tension is notoriously difficult to evenly spread in concrete, resulting that stearic acid-modified concrete frequently experiences a significant reduction in its mechanical qualities as well as challenges in reaching the desired level of hydrophobicity. 24 The emulsification of stearic acid is a very effective solution to the issue of the inadequate dispersion in cement. 25,26 Wang et al added a low-cost aqueous stearic acid emulsion (SAE) of commercial grade to cement mortar (CM).…”
Section: Introductionmentioning
confidence: 99%